Analysis Of Business Feasibility Study On Cv Kandang Malang Pullet Malang - Nisrina Antika; Nimas Vina Tri Novilia; Najib Ulum; Nayla Alista Syahira (Jurnal Multidisiplin West Science, 2022)
This research will discuss the business development of CV Kandang Malang Pullet in Malang. The purpose of this study was to determine the business feasibility of CV Kandang Malang Pullet. The choice of this research location is because the business takes advantage of a market niche with great potential in the market. This business feasibility study is reviewed from legal, environmental, marketing, technical, management and financial aspects. Qualitative methods were used in collecting data for this study using interviews with business people and observation. The legal aspect discusses what legal provisions are needed and the accuracy of the form of a business entity with a business idea. The environmental aspect identifies the strengths and weaknesses of the company as well as the opportunities and threats faced by the company. Marketing aspects are analyzed using STP and marketing mix to assess marketing performance in supporting the development of the business being carried out. Technical aspects are directly related to the company's operations. The management aspect studies matters relating to the management plan and business implementation. The financial aspect analyzes business finances to consider existing risks. The results of this study state that the business feasibility of CV Kandang Malang Pullet Malang is declared feasible in 2022 based on these six aspects. The financial aspect analyzes business finances to consider existing risks. The results of this study state that the business feasibility of CV Kandang Malang Pullet Malang is declared feasible in 2022 based on these six aspects. The financial aspect analyzes business finances to consider existing risks. The results of this study state that the business feasibility of CV Kandang Malang Pullet Malang is declared feasible in 2022 based on these six aspects.